Growth resilience of Pinus latteri to extreme drought events across aridity gradients in southern Laos - Dao-Xiong Gao; Nakhonekham Xaybouangeun; Zaw Zaw; Rao-Qiong Yang; Ze-Xin Fan (Global Ecology and Conservation)
The growth resilience of trees to extreme droughts is not well understood, which hinders the development of effective strategies for sustainable forest management. This study developed tree ring-width chronologies across three sites along aridity gradients in southern Laos and assessed the growth resilience of Pinus latteri to severe droughts and the main climatic drivers. The results indicated that pine trees in the drier site (Mounlapamok, MM) experienced greater decline and higher recovery compared to those in the wetter sites (Dong Phou Vieng, DPV, and Xe sap, TX). Over 79 % of trees resumed their growth levels prior to the drought within one year after the event, and nearly full recovery was observed within two years across all sites. The relationship between tree resistance and recovery demonstrated a closer fit to the theoretical “line of full resilience” at the MM and TX sites, highlighting a higher recovery potential for P. latteri in these environments. Trees with larger age and size exhibited higher resistance to drought stress, especially under better pre-drought moisture conditions. In contrast, trees with higher pre-drought growth rates showed lower resistance, but high recovery especially those experiencing favorable post-drought moisture conditions. However, the increased drought severity adversely affects the resilience of P. latteri. These findings reveal the interactive effects of climate factors and tree-specific traits on the growth resilience of P. latteri in Laos to extreme droughts, offering valuable insights for sustainable forest management practices.